Identification of many crystal forms of Aspergillus nidulans dehydroquinate synthase. - Nichols, C; Ren, J; Lamb, H; Haldane, F; Hawkins, A; Stammers, D (2001)
Extensive crystallization trials of Aspergillus nidulans dehydroquinate synthase, a potential novel target for antimicrobial drugs, in complexes with different ligands have resulted in the identification of nine crystal forms. Crystals of unliganded DHQS, binary complexes with either the substrate analogue, carbaphosphonate or the cofactor NADH, as well as the ternary DHQS-carbaphosphonate-cofactor complex, were obtained. The ternary complex crystallizes from ammonium sulfate and CoCl(2) in space group P2(1)2(1)2, with unit-cell parameters a = 133.8, b = 86.6, c = 74.9 A. The binary carbaphosphonate complex crystallizes from PEG 6000 in space group P2(1)2(1)2(1), with a = 70.0, b = 64.0, c = 197.6 A, and the binary cofactor complex crystallizes from PEG 3350 and sodium potassium tartrate in space group P2(1), with a = 83.7, b = 70.4, c = 144.3 A, beta = 89.2 degrees. DHQS in the absence of ligands crystallizes in space group P2(1), with a = 41.0, b = 68.9, c = 137.7 A, beta = 94.8 degrees. Each of these crystal forms are suitable for high-resolution structure determination. Structures of a range of DHQS-ligand complexes will be of value in the structure-based design of novel antimicrobial drugs.